دور رئيس البرنامج في تحسين جودة برنامج الإعداد اللغوي بجامعة الراية على أساس إدارة الجودة الشاملة - Mukhlishoh Mukhlishoh; Nuril Mufidah; Abdul Malik Karim; Muhammad Khanif (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2022)
Attention to the quality and perfection of work is what draws the attention of the institution these days, such as education, as it is organized by a system adopted by improvement and development. The objectives of this research are two, namely (1) knowing the role of the head of the intensive program for teaching Arabic language for linguistic preparation at Ar-raayah Sukabumi University on the basis of total quality management, (2) knowing the factors affecting the success of the intensive program for teaching Arabic language for linguistic preparation at Ar-raayah Sukabumi University. This research used the qualitative approach, the case study method, and data collection through personal interviews, field observation, and document analysis. Data analysis started from analyzing the data from the process of collecting, sorting, presenting and then drawing conclusions from it The results of this research are, first: the role of the program leader is to plan for quality in conducting consultations, drawing up the academic calendar, arranging files, monitoring quality in the daily follow-up of students, teachers, courses and tests, and improving quality in conducting meetings with teachers, and carrying out continuous training on teachers, and reinforce them. Second: As for the factors that affect the success of the program, they are divided into the obstacle factor, which is the slowness in obtaining electronic devices, and the supporting factor, which is the appropriate administrative organization for the conditions of students. The conclusion of this research indicates that the total quality management system generates an excellent program for teaching the Arabic language